IPhone and iOS 4 advanced app development : learn by video - Turall, Robert (Peachpit Press, 2011)
"This innovative product uses interactive video to show iOS developers how to integrate rich features that end-users have come to expect from apps, using the iOS Core Location and Mapping features and camera data. This video reviews the main features of XCode 4 as well as the more advanced APIs available to developers. Retrieving and creating address book and calendar data within the app is also covered, as well as manipulating media files, including photos and video. Creating Universal Apps will let users broaden their audiences to the iPhone, iPod Touch, and iPad. Experienced instructor Robert Turall presents up to four hours of exceptional video training, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside the video. Project files used in the lessons are included on the disc so viewers can practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.